Regional Variation in Androgen Receptor Expression and Biomechanical Properties May Contribute to Cryptorchidism Susceptibility in the LE/orl Rat - Morgan, Joshua T.; Robbins, Alan K.; Mateson, Abigail B.; Sawamoto, Kazuki; Tomatsu, Shunji; Gray, Dione R.; Gleghorn, Jason P.; Barthold, Julia Spencer (Frontiers in Endocrinology, 2018)
Background: The process of testicular descent requires androgen and insulin-like 3, hormones secreted by fetal Leydig cells. Knowledge concerning distinct and common functions of these hormones in regulating development of the fetal gubernaculum remains limited and/or conflicting. The current studies were designed to better define characteristics of androgen receptor (AR) expression, function and regulation, as well as the biomechanical properties of normal and cryptorchid gubernaculum during fetal development. Methods: We studied fetal gubernacula from Long Evans outbred (LE/wt) rats and an inbred (LE/orl) strain with an inherited form of cryptorchidism associated with an AR signaling defect. Gubernacular cells or whole organs obtained from LE/wt and LE/orl fetal gubernacula underwent AR immunostaining and quantitative image analysis. The effects of dihydrotestosterone (DHT) on AR expression, muscle fiber morphology, hyaluronan (HA) levels and glycosaminoglycan (GAG) content were measured in LE/wt gubernacula. Finally, the spatial mechanics of freshly harvested LE/wt and LE/orl fetal gubernacula were compared using micropipette aspiration. Results: AR is expressed in the nucleus of mesenchymal core, tip and cord cells of the embryonic (E) day 17 and 21 fetal gubernaculum, and is enhanced by DHT in primary cultures of gubernacular mesenchymal cells. Enhanced AR expression at the tip was observed in LE/wt but not LE/orl gubernacula. In in vitro studies of whole mount fetal gubernaculum, DHT did not alter muscle fiber morphology, HA content or GAG production. Progressive swelling with reduced cellular density of the LE/wt gubernaculum at E19–21 was associated with increased central stiffness in LE/wt but not in LE/orl fetuses. Conclusions: These data confirm nuclear AR expression in gubernacular mesenchyme with distal enhancement at the tip/cord region in LE/wt but not LE/orl rat fetuses. DHT enhanced cellular AR expression but had no major effects on muscle morphology or matrix composition in the rat fetal gubernaculum in vitro. Regional increased stiffness and decreased cell density between E19 and E21 were observed in LE/wt but not LE/orl fetal gubernacula. Developmental differences in cell-specific AR expression in LE/orl fetal gubernacula may contribute to the dysmorphism and aberrant function that underlies cryptorchidism susceptibility in this strain.